The Effect of Social Capital and Husband-wife Interaction on Marital Quality among Families in Early Years and Middle Years Marriage - Dewi, Egretta Melistantri; Puspitawati, Herien; Krisnatuti, Diah (Journal of Family Sciences, 2018)
This study aims to analyze the effect of social capital and husband-wife interaction on marital quality among families in early years and middle years marriage. The study was using cross sectional design. The selection of research sites was purposively chosen in Bogor City. The location of the study was in Kebon Pedes and Kedung Badak, regions of Tanah Sareal district. Samples of this study were 120 families in early and middle years of marriage with wives as the main participants. Data were collected through interview using questionnaire. The study found that social capital in families with early marriage age in the intermediate category, and in families with middle years of marriage is in the high category. Different test results show only in the dimensions of gender partnerships that families in middle years of marriage were higher than early years families. On variable of husband-wife interaction, half of the families with early marriage years were in the intermediate category and more than half of families with middle years of marriage were in the high category. There wereno significant differences in all dimensions of husband and wife interaction. In the variable quality of marriage, half of families with early years marriage were in the intermediate category, whereas more than half of families with middle years marriage were in high category. There wereno significant differences in all dimensions of marital quality.